Pengaruh PDRB Per Kapita dan Tingkat Kemiskinan Terhadap Tingkat Partisipasi Sekolah di Provinsi Riau - Khalis, Nur; Amri, Khairul (Yayasan Kawanad, 2024)
The aim of this research is to analyze the relationship between GRDP per capita and poverty levels on district/city school enrollment rates in Riau province. Using secondary data in the form of a panel of 12 districts/cities in Riau province from the 2015-2022 period. The research method used is panel data regression. The results of research using the Fixed Effect model approach show that the relationship between GRDP per capita has a positive and insignificant effect on school enrollment rates and the poverty level has a negative and significant relationship with school enrollment rates in districts/cities in Riau province.